Inferences about the population history of Rangifer tarandus from Y chromosome and mtDNA phylogenies - Bozlak, Elif; Pokharel, Kisun; Weldenegodguad, Melak; Paasivaara, Antti; Stammler, Florian; Røed, Knut H.; Kantanen, Juha; Wallner, Barbara (Wiley-Blackwell, 2024)
Reindeer, called caribou in North America, has a circumpolar distribution and all extant populations belong to the same species (Rangifer tarandus). It has survived the Holocene thanks to its immense adaptability and successful coexistence with humans in different forms of hunting and herding cultures. Here, we examine the paternal and maternal history of Rangifer based on robust Y-chromosomal and mitochondrial DNA (mtDNA) trees representing Eurasian tundra reindeer, Finnish forest reindeer, Svalbard reindeer, Alaska tundra caribou, and woodland caribou. We first assembled Y-chromosomal contigs, representing 1.3 Mb of single-copy Y regions. Based on 545 Y-chromosomal and 458 mtDNA SNPs defined in 55 males, maximum parsimony trees were created. We observed two well separated clades in both phylogenies: the “EuroBeringian clade” formed by animals from Arctic Islands, Eurasia, and a few from North America and the “North American clade” formed only by caribou from North America. The time calibrated Y tree revealed an expansion and dispersal of lineages across continents after the Last Glacial Maximum. We show for the first time unique paternal lineages in Svalbard reindeer and Finnish forest reindeer and reveal a circumscribed Y haplogroup in Fennoscandian tundra reindeer. The Y chromosome in domesticated reindeer is markedly diverse indicating that several male lineages have undergone domestication and less intensive selection on males. This study places R. tarandus onto the list of species with resolved Y and mtDNA phylogenies and builds the basis for studies of the distribution and origin of paternal and maternal lineages in the future.
Keywords: fylogenetiikka; poro; metsäpeura; Y-kromosomi; sekvenssianalyysi; perimä; peura (laji); reindeer (domestic); reindeer (species); Y-chromosome; mitochondrial DNA; haploryhmä; haplogroup; sequence analysis; genome; phylogenetics